Dual intervention of Boeravinone B and Chebulinic Acid mitigates BHT-Induced toxicity in HepG2 cells: modulating apoptosis and autophagy - Samidha S. Kakade; Harshad K. Bote; Pankaj K. Pawar (Scientific Reports)
Abstract Butylated Hydroxytoluene (BHT) is found to exert cellular toxicity through induction of oxidative stress although being used as antioxidant in many food products. This study investigates the protective effects of two herbal compounds Boeravinone B (BB) and Chebulinic acid (CA) in combination (B4C3 i.e. BB 4 µg/mL and CA 3 µg/mL). Key findings revealed that BHT exerted toxicity through induction of ROS (234.47 a.u.) and RNS (0.042 µM/mL), but B4C3 has significantly reduced it (115.46 a.u. and 0.018 µM/mL respecctively). BHT exposure raised the activities of antioxidant enzymes such as SOD (70.9%), CAT (7.08 units/mL), GPX (1.21 units/mL), levels of protein carbonyls (3.52 units/mg) and lipid peroxides (418.34%). Whereas treatment with B4C3 decreased the levels of SOD (29.92%), CAT (3.12 units/mL), GPX (0.36 units/mL), protein carbonyls (0.91 units/mg of protein) and lipid peroxides (106.67%) during BHT exposure. It was found that 20.56% cells were apoptotic while 73.83% were autophagic during BHT treatment. However, proposed phytotherapy rescued the cells from apoptotic and autophagic death and supported cell growth which was confirmed by RT-PCR and growth analysis. Collectively, B4C3 offered a significant protection against BHT-induced cellular damage, suggesting its potential as therapeutic agents for oxidative stress-related hepatotoxicity.